2021
DOI: 10.3390/biomedicines9101495
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain after Interferon-Free Treatment of Chronic Hepatitis C—Results from the German Hepatitis C-Registry (DHC-R)

Abstract: Chronic hepatitis C can be treated very effectively with direct-acting antivirals (DAA) with only minor side effects compared to an interferon-containing treatment regimen. The significance of metabolic comorbidities after HCV cure is not well defined. This study aims to investigate short- and long-term weight change of patients receiving interferon-free antiviral treatment for chronic hepatitis C. The German Hepatitis C-registry (DHC-R) is a national multicenter real-world cohort. A total of 5111 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Weight change was defined as the difference between weight at the baseline and at SVR12. The weight gain was considered as weight change ≥ 1 kg from the baseline to SVR12, and this was chosen to be clinically significant [22].…”
Section: Clinical and Laboratory Assessmentmentioning
confidence: 99%
“…Weight change was defined as the difference between weight at the baseline and at SVR12. The weight gain was considered as weight change ≥ 1 kg from the baseline to SVR12, and this was chosen to be clinically significant [22].…”
Section: Clinical and Laboratory Assessmentmentioning
confidence: 99%
“…Notably, there was no correlation between steatosis and fibrosis alterations in this study, which might be explained by short-term follow-up after DAA treatment and the occurrence of new-onset steatosis in some patients. Indeed, previous studies in Western populations have demonstrated that weight gain is commonly occur during long-term follow-up after HCV cure with DAAs [ 43 , 44 ]. For instance, a large prospective study of 11,000 veterans in the U.S. indicated that at least 20% of treated patients had excess weight gain within 2 years of achieving SVR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a large prospective study of 11,000 veterans in the U.S. indicated that at least 20% of treated patients had excess weight gain within 2 years of achieving SVR [ 43 ]. A recent report from Germany also showed that a substantial weight gain was identified in one-third of HCV-infected patients, particularly among non-obese individuals [ 44 ]. Additionally, in the mentioned report the progressive weight gain became more evident during long-term follow-up, while no significant weight change was observed early after completing DAA therapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-DAA diabetes increases mortality and liver-related events independently of HCV cure [ 12 ], and diabetes is also an independent risk factor of de novo hepatocellular carcinoma after DAA treatment [ 16 ]. Weight gain is likely to occur after DAA treatment [ 17 ], while the impact of overweight and obesity on post-HCV cure cirrhosis and hepatocellular carcinoma development remain unclear [ 12 , 18 ]. There is no hard evidence for the benefit of DAA-based HCV cure on elevated blood pressure [ 19 ], and the long-term impact of DAA therapy on serum lipid needs to be investigated [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%